A new non-convex model of the binary asteroid (809) Lundia obtained with the SAGE modelling technique. Issue 1 (1st July 2017) - Bartczak, P.; Kryszczyńska, A.; Dudziński, G.; Polińska, M.; Colas, F.; Vachier, F.; Marciniak, A.; Pollock, J.; Apostolovska, G.; Santana-Ros, T.; Hirsch, R.; Dimitrow, W.; et al.
Abstract: We present a new non-convex model of the binary asteroid (809) Lundia. A SAGE (Shaping Asteroids with Genetic Evolution) method using disc-integrated photometry only was used for deriving physical parameters of this binary system. The model of (809) Lundia improves former system's pole solution and gives the ecliptic coordinates of the orbit pole – λ = 122°, β = 22°, σ = ±5° – and the orbital period of 15.415 74 ± 0.000 01 h. For scaling our results, we used an effective diameter ( D eff ) of 9.6 ± 1.1 km obtained from Spitzer observations. The non-convex shape description of the components permitted a refined calculation of the components' volumes, leading to a density estimation of 2.5 ± 0.2 g cm −3 and a macroporosity of 13–23 per cent. The intermediate-scale features of the model may also offer new clues on the components' origin and evolution.